2005
DOI: 10.1111/j.1745-4573.2005.01204.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium Chloride Marination and Collagen Content on Beef, Horse, Rabbit and Hen Meat Hardness

Abstract: Overall, meat texture is composed of two types of toughness: primary toughness, because of mechanical resistance of the myofibrillar structure, and secondary toughness, by reason of connective tissue content. Primary toughness can be reduced during aging by intrinsic and extrinsic protease activity. Secondary toughness is determined by a given amount of epimysial and perimysial connective tissue, which cannot be reduced as no collagenases are naturally present in the muscle or produced by native meat microbial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…; Pérez‐Chabela et al . ). In the present study, the shear force of horse meat and beef pastirma were not different.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…; Pérez‐Chabela et al . ). In the present study, the shear force of horse meat and beef pastirma were not different.…”
Section: Resultsmentioning
confidence: 97%
“…1). Horse meat has been reported to be tougher than beef (Pérez et al 1998;Pérez-Chabela et al 2005). In the present study, the shear force of horse meat and beef pastirma were not different.…”
Section: Shear Forcementioning
confidence: 99%
“…Different compounds have been used for marinating horse meat, to achieve improved texture parameters. Studies [ 43 ] on similar material showed that CaCl 2 solution used for marinating contributed to lowering the hardness of meat samples in comparison to the control samples.…”
Section: Resultsmentioning
confidence: 99%
“…A few studies have comprehensively analyzed the influence of horse age, marinating substances, and period of frozen storage on the quality of horse meat. Those studies [ 17 , 37 , 38 , 39 , 40 , 41 , 42 , 43 ] contribute to our understanding of how to improve the quality of horse meat, and ultimately increase the demand from consumers and meat processing plants. Nevertheless, there is still a need for further research to increase knowledge regarding this topic.…”
Section: Introductionmentioning
confidence: 99%
“…Calcium chloride, as an activator of proteolysis in meat of slaughter animals, is introduced mostly during injection or marinating [58,59]. Research aimed at improving the quality of horsemeat using CaCl 2 was carried out by, among others, Pérez-Chabela et al [60], Pérez-Chabela et al [61], Pérez-Chabela et al [62] and Pérez et al [63]. The use of 150 mM calcium chloride solution for marinating horsemeat for 48 h caused the activation of calpains, thus affecting the degradation of myofibrillar proteins and improving the tenderness of the analyzed meat [60].…”
Section: The Use Of Calcium Saltsmentioning
confidence: 99%